Customer encounters on twitter : a study of positive evaluation and complaint management on english corporate profiles - Tereszkiewicz, Anna (Jagiellonian University Press, 2020)
The book presents a discussion of the selected properties of customer encounters conducted on brand profiles on Twitter. The first part of the book discusses social media and their use in corporate communication, with a particular consideration of Twitter. It also defines customer encounters as a genre of interaction and presents an overview of previous research devoted to this area of communication. The second part of the publication concerns corporate profiles on Twitter and customer encounters conducted in this medium. The author characterizes consumer messages containing positive evaluation and complaints posted on company profiles. The strategies which companies use in response to positive and negative evaluations are discussed in detail. The publication also contains a description of selected conventional politeness acts used in the interaction as well as the language properties of tweets on the lexical and syntactic level. The discussion presented in the book shows Twitter as an important tool of image management and customer interaction.